(untitled) (Iranian Journal of Kidney Diseases, 2013)
Leakage of small amounts of proteins in urine has been considered since 1980s a crucial sign of early kidney disease, especially in diabetic patients. An increasing interest in microalbuminuria as a cardiovascular risk marker has been more recently considered. Many studies linked microalbuminuria to early cardiovascular disease, as a marker of endothelial dysfunction, not only in diabetic patients, but also in hypertensive patients and in general population. Microalbuminuria is considered nowadays by guidelines as a cost-effective marker of subclinical organ damage in hypertensive patients and should be checked routinely in hypertensive patients. Assessing subclinical organ damage is recommended not only at the level of screening, but also during treatment. Microalbuminuria is also considered as a treatment outcome marker and useful for understanding the ability of a given therapeutic intervention to regress organ damage or slow down its progression.